EVALUASI KEBIJAKAN PROGRAM JAMINAN KESEHATAN NASIONAL (JKN) BERDASARKAN UNDANG-UNDANG NO. 40 TAHUN 2004 TENTANG SISTEM JAMINAN SOSIAL NASIONAL - Jackson Yumame (CV. Adiba Aisha Amira, 2025)
The National Health Insurance Program (JKN) regulated by Law No. 40 of 2004 concerning the National Social Security System (SJSN) is a strategic step by the Indonesian government to provide comprehensive health protection for the entire community. This study aims to evaluate the effectiveness of the implementation of the JKN policy by highlighting the alignment of implementation with the principles and legal mandates of the SJSN. The research method used is a literature review. The evaluation results indicate that the JKN has expanded coverage and access to health services, particularly for vulnerable groups. However, several challenges remain, such as administrative barriers, disparities in health facilities between regions, and quality and financing constraints. The recommendations emphasise the need for improved governance, harmonisation of central and regional regulations, digitalisation of services, and strengthening of the education and supervision systems to ensure that the principles of equity and equity in health services are realised in a sustainable manner in accordance with the mandate of Law No. 40 of 2004.